(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The exchange rate, which represents the price of one currency in terms of another, plays a pivotal role in the global market’s open economies. It exerts a substantial influence on the overall economic performance and growth of a nation. Consequently, the correlation between the exchange rate and the macroeconomic factors associated with its fluctuations holds significant importance for any open economy. Exchange rates are among the most critical factors influencing a country’s economic growth, directly impacting international trade. This study delves into the repercussions of various macroeconomic variables, including the Current Account Deficit (CAD), imports, exports, and Purchasing Power Parity (PPP), on the volatility of the US Dollar to Indian Rupee (USD to INR) exchange rate in India. The research aims to explore the long and short-term relationships between these variables and exchange rates. Various statistical tests, such as the Augmented Dickey-Fuller (ADF) test, stationary testing, stability testing, Johansen co-integration test, and Granger causality test, have been applied to decipher how these variables affect the exchange rate. Additionally, the study employs the ARIMA (Auto Regressive Integrated Moving Average) method for forecasting the future movements of exchange rates over a specific time horizon. Notably, when the country’s CAD is effectively managed, it has an automatic control mechanism on the exchange rate, mitigating its impact on other economic variables. In today’s globalized landscape, a nation’s exchange rate assumes a paramount role, reflecting the stability and robustness of its economy. While exchange rates are primarily determined by the supply and demand for a nation’s currency in the international market, various macroeconomic factors have been identified to exert influence, particularly in developing countries like India. A comprehensive comprehension of these factors serves as an authentic indicator of exchange rate movements. This study seeks to ascertain the impact of several macroeconomic variables, such as fluctuations in crude oil prices, GDP, Consumer Price Index (CPI), major capital market indices like BSE Sensex, and gold prices, on the exchange rate of the Indian currency.